Analisis Keuangan dan Sumber Daya Manusia terhadap Efisiensi Blud di Puskesmas Mantup - Shidayatri, Herwidhiyah; Kadarisman, Sumeidi; Yuliaty, Farida; Paramartha, Vip; Rulia, Rulia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The implementation of the Regional Public Service Agency (BLUD) in community health centers provides high flexibility, accelerates response time to meet community needs in the field of health services, and becomes an institution that best understands these dynamics. This study aims to analyze the development of community health center management, especially in the aspects of financial governance and human resources. Financial analysis is carried out based on Liquidity, Solvency, and Profitability indicators, while the HR aspect is analyzed through productivity and the number of HR at the Mantup Community Health Center, Lamongan Regency, East Java Province, using financial and HR data from 2015 to 2024. The results of the analysis show that the implementation of BLUD Financial Management (PPK) has increased in trend, while from the HR side, Mantup Community Health Center does not require a significant increase in the number of HR for BLUD. Overall, there is a simultaneous influence between the PPK BLUD financial and HR perspectives on technical efficiency at the Mantup Community Health Center, except in terms of productivity.